Coagulation Biomarkers in Healthy Chinese-Origin Rhesus Macaques (Macaca mulatta) - Frydman, Galit H (J Am Assoc Lab Anim Sci, 2016)
Rhesus macaques (Macaca mulatta) are a common model for the study of human biology and disease. To manage coagulopathies in these animals and to study their clotting changes, the ability to measure coagulation biomarkers is necessary. Currently, few options for coagulation testing in NHP are commercially available. In this study, assays for 4 coagulation biomarkers—D-dimer, antithrombin III, protein C, and soluble P-selectin—were developed and optimized for rhesus macaques. Whole blood was collected from 28 healthy Chinese-origin rhesus macaques (11 male; 17 female) ranging in age from 5 to 20 y. Coagulation biomarkers were measured by using bead-based sandwich ELISA technology. The ranges (mean ± 90% confidence interval) for these biomarkers were: antithrombin III, 124.2 to 133.4 μg/mL; protein C, 3.2 to 3.6 μg/mL; D-dimer, 110.3 to 161.3 ng/mL; soluble P-selectin, 0.12 to 0.14 ng/10(6) platelets. These reference values did not differ significantly according to sex or age. These new assays for coagulation biomarkers in rhesus macaques will facilitate the evaluation of in vivo hemostasis.